Application of drones in solving EHS tasks - Zákányi, Balázs Zsolt; Horváth, Gábor Károly; Zákányiné Mészáros, Renáta (International Journal of Engineering and Management Sciences, 2019)
Drones or unmanned aerial vehicles (UAVs) or unmanned aerial systems (UAS) are unmanned aerial vehicles without pilot and passenger on board. These tools have been used primarily in the military, but have now grown significantly in applications including industrial use, services, disaster management, and the civilian sector. We briefly introduce the most important classification criteria for drones. In addition, in this study, we have collected the uses that the industry and the EHS sector can or will use in the future. We mention the most important drone-mounted and mountable accessories that can be used by users for their specific tasks.